Increased Precision in County-Level Volume Estimates in the United States National Forest Inventory With Area-Level Small Area Estimation - Cao, Qianqian; Dettmann, Garret T.; Radtke, Philip J.; Coulston, John W.; Derwin, Jill; Thomas, Valerie A.; Burkhart, Harold E.; Wynne, Randolph H. (Frontiers in Forests and Global Change, 2022)
Many National Forest Inventory (NFI) stakeholders would benefit from accurate estimates at finer geographic scales than what is currently possible using NFI sample data. In the past decade small area estimation (SAE) techniques have been shown to increase precision in forest inventory estimates by combining field observations and remote-sensing. We sought to demonstrate the potential for improving the precision of forest inventory growing stock volume estimates for counties in U.S. states of North Carolina, Tennessee, and Virginia, by pairing canopy height models from digital aerial photogrammetry and field plot data from the U.S. NFI. Area-level Fay-Herriot estimators were used to avoid the need for precise (GPS) coordinates of field plots. Reductions in standard errors averaging 30% for North Carolina county estimates were observed, with 19% average reductions in standard errors in both Tennessee and Virginia. Accounting for spatial autocorrelation among adjacent counties provided further gains in precision when the three states were treated as a single forest land population; however, analyses conducted one state at a time showed that good results could be achieved without accounting for spatial autocorrelation. Apparent gains in sample sizes ranged from about 65% in Virginia to 128% in North Carolina, compared to the current number of inventory plots. Results should allow for determining whether acquisition of statewide digital aerial photogrammetry would be cost-effective as a means for increasing the accuracy of county-level forest volume estimates in the U.S. NFI.